Developing the algorithm for an online community monitoring with the aim of manipulation detection - Peleschyshyn, Andrij; Holub, Zoriana (Lviv Polytechnic Publishing House, 2016)
In this paper the algorithm for online community monitoring with the aim of informational and psychological manipulation detection is suggested. The algorithm is designed to boost the efficiency of the process of detecting manipulation. It consists of three block of actions directed at detecting suspicious profiles, sorting and detecting manipulation.
Keywords: online community; informational and psycholo-gical manipulation; suspicious profile; manipulation tactic